Dynamic garbage collection scheme based on past update times for NAND flash-based consumer electronics - Lin, Mingwei; Yao, Zhiqiang (IEEE transactions on consumer electronics, 2015)
NAND flash memory has become the dominant storage device for consumer electronics such as smart phones, portable personal computers, and digital cameras. Because NAND flash memory often introduces an out-of-place update scheme to solve its erase-before-write hardware constraint, these consumer electronics devices should perform garbage collection to reclaim garbage and obtain free space. However, existing garbage collection schemes usually suffer from the high garbage collection overhead and the high degree of wear leveling. In this paper, a dynamic garbage collection scheme based on past update times is proposed for NAND flash-based consumer electronics. The proposed scheme can achieve a balance between the garbage collection overhead and the degree of wear leveling. Experimental results show that the proposed scheme is better than existing garbage collection schemes in terms of the number of copy operations, the number of erase operations, the energy consumption, and the degree of wear leveling.